2019
DOI: 10.1016/j.meegid.2018.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the virulence and genomics of Aeromonas salmonicida strains isolated from human patients

Abstract: The bacterium Aeromonas salmonicida is known since long time as a major fish pathogen unable to grow at 37°C. However, some cases of human infection by putative mesophilic A. salmonicida have been reported. The goal of the present study is to examine two clinical cases of human infection by A. salmonicida in Spain and to investigate the pathogenicity in mammals of selected mesophilic A. salmonicida strains. An evaluation of the pathogenicity in a mouse model of clinical and environmental A. salmonicida strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 63 publications
3
44
0
Order By: Relevance
“…The important fish pathogens species are A. salmonicida and A. hydrophila, which particularly affect salmonids, causing ulcers, hemorrhages, furunculosis, and septicemias [7,45]. These infections cause important financial losses in the aquaculture industry [4,7,16,45,88]. In fact, Rasmussen-Ivey et al [138] described a hypervirulent A. hydrophila strain as a causative agent of worldwide outbreaks in warm-water fishes.…”
Section: Aeromonas In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The important fish pathogens species are A. salmonicida and A. hydrophila, which particularly affect salmonids, causing ulcers, hemorrhages, furunculosis, and septicemias [7,45]. These infections cause important financial losses in the aquaculture industry [4,7,16,45,88]. In fact, Rasmussen-Ivey et al [138] described a hypervirulent A. hydrophila strain as a causative agent of worldwide outbreaks in warm-water fishes.…”
Section: Aeromonas In Animalsmentioning
confidence: 99%
“…Studies have so far reported that 96.5% of the strains associated to clinical cases were identified as one of only four species: Aeromonas caviae (29.9%), Aeromonas dhakensis (26.3%), Aeromonas veronii (24.8%), and Aeromonas hydrophila (15.5%) [5,15]. In addition, other species usually linked with fish diseases, such as Aeromonas salmonicida, have also been reported in human infections [16]. Moreover, one important issue in the study of these infections is the selection of an adequate animal model or cell line that would reproduce the pathogenicity of Aeromonas [17].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular phylogeny was used to determine the phylogenetic position of strain JF2480 among the other A. salmonicida. To do this, the genomic sequence of strain JF2480 was added to a dataset comprising a representative of each of the Aeromonas species, all sequences from mesophilic A. salmonicida and the sequences of representatives of all psychrophilic subspecies of A. salmonicida (Table S1) [18]. All the 55 genome sequences were annotated using Prokka version 1.13.3 [22].…”
Section: Sequence Assembly and Analysesmentioning
confidence: 99%
“…This was the case with the characterization of four Indian mesophilic A. salmonicida strains (Y47, Y567, Y577, A527) from undetermined subspecies and isolated from contaminated food [10][11][12]. Mesophilic A. salmonicida strains with human clinical background were also reported in Europe and India, including from a 68-year-old diabetic woman on continuous ambulatory peritoneal dialysis with abdominal pain and cloudy peritoneal fluid, in the blood of a 34-year-old female patient, from the skin infection of a 67-year-old immunocompetent male, in the right eye of a 55-year-old female who had recovered from cataract surgery, from a 15-year-old boy who had recovered from a finger surgery, from the feces of a child suffering from acute gastroenteritis, and finally from a person having cellulitis in a foot following trauma [13][14][15][16][17][18]. However, the pathogenicity of the isolates from human cases was not clearly demonstrated until a very recent study clearly showed the capacity of mesophilic A. salmonicida strains to infect mammals by doing infection experiments on mice [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation